Geometry-Induced Tuning of Ferromagnetic Resonance in Asymmetric Nanowires - Saavedra-Díaz, E (Institute of Physics, 2025)
The interplay between magnetic interactions at the nanoscale yields several geometry-induced effects on the magnetic properties of nanoparticles. In this work, using numerical simulations, we analyze the influence of shape on the equilibrium state and the dynamic response of magnetization to a magnetic field in asymmetric Ni nanowires. Depending on geometric and magnetic parameters, two equilibrium states emerge in such particles, the flower and twisted flower states. The nucleated magnetic configuration is determined by the asymmetry degree of the nanowire. These states are defined by the orientation of magnetic moments in the top and bottom regions of the nanowire, while the shape anisotropy ensures a monodomain in the bulk. Concerning the dynamical response, the number and frequencies of the peaks correlate with the minimum energy configuration. Our findings provide a basis for controlling frequency spectra in magnetic nanowires through precise adjustments of geometric parameters. © 2025 IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.